2019
DOI: 10.3390/v11020123
|View full text |Cite
|
Sign up to set email alerts
|

Sediments from Arctic Tide-Water Glaciers Remove Coastal Marine Viruses and Delay Host Infection

Abstract: Over the past few decades, the Arctic region has been strongly affected by global warming, leading to increased sea surface temperatures and melting of land and sea ice. Marine terminating (tide-water) glaciers are expected to show higher melting and calving rates, with an increase in the input of fine sediment particles in the coastal marine environment. We experimentally investigated whether marine viruses, which drive microbial interactions and biogeochemical cycling are removed from the water column throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 55 publications
(93 reference statements)
1
28
0
Order By: Relevance
“…This is perhaps not surprising as different taxonomic groups may respond differently to perturbations from glacier discharge leading to changes in food web dynamics. For example, highly turbid glacial waters have particularly strong negative effects on filter-feeding (Arendt et al, 2011;Fuentes et al, 2016) and phagotrophic organisms (Sommaruga, 2015) and may also lead to reduced viral loads in the water column due to adsorption onto particle surfaces (Maat et al, 2019).…”
Section: Organic Matter In Glacial Dischargementioning
confidence: 99%
“…This is perhaps not surprising as different taxonomic groups may respond differently to perturbations from glacier discharge leading to changes in food web dynamics. For example, highly turbid glacial waters have particularly strong negative effects on filter-feeding (Arendt et al, 2011;Fuentes et al, 2016) and phagotrophic organisms (Sommaruga, 2015) and may also lead to reduced viral loads in the water column due to adsorption onto particle surfaces (Maat et al, 2019).…”
Section: Organic Matter In Glacial Dischargementioning
confidence: 99%
“…To achieve these goals, during the 2019 austral summer in the Admiralty Bay in West Antarctica, recurrent plumes in front of four glaciers, which differ in shape, dynamics, and geological location, were investigated, and their plume waters were examined. A large glacial sediment discharge has an impact on the salinity and temperature of seawater [4], biodiversity, the productivity as well aswell-being of marine flora and fauna, and, dependent on the latter, land animals and birds [19][20][21][22][23][24][25]. Consequently, changes in polar ecosystems require monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Another suggested effect of glacier sediment is the adsorption of viruses to these particles (De Corte et al 2011, Maat et al 2019. Viruses are parasites that use the metabolism of the host to propagate.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, only little is known on the ecological relevance of virus to sediment adsorption, especially for the rapidly warming polar waters. Only very recently, it was experimentally demonstrated that different virus populations, including an Arctic phycovirus, strongly adsorb to glacier-derived fine-sediment (up to 90%; Maat et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation